Simulation of assembly and disassembly behavior of ring-type snap fits. (March 2019) - Frick, A; Boßler, R; Brehm, M; Lang, F
In many plastics engineering applications, fastenings are typically realized by means of snap fits instead of conventional types of fasteners such as screwed fits or rivets. Snap fits can be easily integrated into injection molded parts and enables later assembly without additional fasteners. When disassembling a ring-type snap fit, the viscous deformation resulting from the hysteresis behavior of the polymeric material can reduce the holding force and the disassembly force. In a conventional finite element analysis of the assembly and disassembly process, the hysteresis behavior is usually not taken into account. After loading and unloading a part, a permanent set after the removal of the load is found, which is due to the viscous material deformation of the polymeric material and yields the accompanying change in deformation behavior under sequence of loading procedures. The first assembly can already lead to mechanical damage of the polymeric part. Consequently, in return it explains why the disassembly forces of a ring-type snap fit are lower than the assembly forces. The reduction of the necessary disassembly force due to mechanical damage reaction needs to be predicted by a simulation of the component. Therefore, the different deformation behavior during assembly and disassembly of the snap fit, which in turn is influenced by the height of the deformation of the snap-in element during assembly, must be taken into account for a simulation. Neglecting to observe this different deformation behavior can result into a malfunction or even failure of the component during application may occur. The simulation possibilities for deformation behavior during force loading and unloading of a polymeric joint is investigated by means of finite element analysis. The assembly and disassembly forces of a ring-type snap fit made of polyoxymethylene were simulated employing three different material constitutive models and compared with experimentally measured results. For the simulation of a subsequent disassembly and further assembly, only a viscoelastic material model satisfactorily predicts the measured behavior of the component in the experiment.